2021
DOI: 10.1108/rpj-09-2020-0224
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite composite scaffold for bone regeneration via rapid prototyping technique: a review

Abstract: Purpose Rapid prototyping (RP) technology is widely used in many fields in recent years. Bone tissue engineering (TE) is an interdisciplinary field involving life sciences, engineering and materials science. Hydroxyapatite (HAp) are similar to natural bone and it has been extensively studied due to its excellent biocompatibility and osteoconductivity. This paper aims to review nanoscaled HAp-based scaffolds with high porosity fabricated by various RP methods for bone regeneration. Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 105 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…In addition, researchers also reported that PLA/nHAP is capable to enhance the osteo‐inductivity and osteo‐conductivity 32 . In vitro studies performed with PLA/nHAp revealed that cell adhesion and proliferation on the surface of the developed biocomposite support the biocompatible nature 25,33 . Thus, the PLA/nHAp biocomposite and membrane 34,35 is helpful in bone tissue repair.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, researchers also reported that PLA/nHAP is capable to enhance the osteo‐inductivity and osteo‐conductivity 32 . In vitro studies performed with PLA/nHAp revealed that cell adhesion and proliferation on the surface of the developed biocomposite support the biocompatible nature 25,33 . Thus, the PLA/nHAp biocomposite and membrane 34,35 is helpful in bone tissue repair.…”
Section: Introductionmentioning
confidence: 97%
“…32 In vitro studies performed with PLA/nHAp revealed that cell adhesion and proliferation on the surface of the developed biocomposite support the biocompatible nature. 25,33 Thus, the PLA/nHAp biocomposite and membrane 34,35 is helpful in bone tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Bone tissue engineering is performed by constructing the three components of artificial bone material, bone cells, and the growth factors required by the cells into a composite and implanting them into the body to reconstruct the tissue externally, internally, and functionally [ 1 ]. At present, the main artificial bones on the market are made of metal materials, bioceramics, and polymer materials.…”
Section: Introductionmentioning
confidence: 99%